The Implementation of Buddy Vocabulary Cards Technique to Improve Reading Comprehension - agus wilson (Scope : Journal of English Language Teaching, 2019)
This research is aimed to propose a model of learning for the English teacher to improve reading comprehension of discourse in English and see whether the Buddy Vocabulary Cards Technique has reached the level of effectiveness to be presented to students. The research was held at SMK AL-MAKMUR in South Jakarta Class 1, the population of 239 students with a sample that is taken randomly about 44 students. Research methods are Library Studies and Field Studies with through debriefing and give some questions. Based on the results, it can be concluded that the Buddy Vocabulary Cards technique can be used to improve students' reading comprehension. The result of study identifies that the average value of the students have achieved good category, with an average value of 6.8.